Marxism today. - Communist Party of Great Britain (London : Communist Party, 1957)
This title comes from the Political Extremism and Radicalism digital archive series which provides access to primary sources for academic research and teaching purposes. Please be aware that users may find some of the content within this resource to be offensive, see our content advisory note at https://go.gale.com/ps/staticResource?userGroupName=nla&inPS=true&prodId=PLEX&type=About.
"Theoretical and discussion journal of the Communist Party."
Reproduction of the originals from Searchlight Archive, University of Northampton.
Although publication officially ceased with Dec. 1991 issue, a "Special issue" was published Nov./Dec. 1998.
Reproduced from source library: v. 3, no. 3 (Mar. 1959) ; v. 3, no. 4 (Apr. 1959) ; v. 3, no. 5 (May 1959).
Keywords: Communism -- Periodicals; Communism; Cultuur; Politiek; Periodicals